Analisis Pemberian Reward dan Punishment sebagai Upaya untuk Pendidikan Karakter Disiplin Siswa Kelas V SDN 2 Suruh - Priya Kusuma Bahari; Richa Okta Barera (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Education, in addition to developing all potentials and achievements, also serves as a place for character formation, one of which is the character of discipline. Discipline character can be developed through the provision of rewards and punishments. This research aims to determine the application of reward and punishment as an effort for character education in discipline for elementary school students. This research was conducted at one of the schools, namely Sekolah Dasar Negeri 2 Suruh, Suruh District, Trenggalek Regency. The type of research conducted is descriptive qualitative research. The research activities were conducted in the form of observation, interviews, and documentation to collect data. The subjects in this study are three fifth-grade elementary school students and their teacher. The results of the research conducted show that the provision of rewards and punishments can bring about positive changes in students. These changes are marked by an improvement in the students' discipline. Thus, the proper implementation of reward and punishment can be a solution for teachers and students to create a conducive learning environment. The importance of collaboration between teachers and in supporting character education discipline is also a key factor in the success of its implementation.